Targeted antimicrobial photodynamic therapy of biofilm-embedded and intracellular staphylococci with a phage endolysins cell binding domain - Bispo, Mafalda (2022)
Antimicrobial resistance is among the biggest threats to mankind today. There are two alternative antimicrobial therapies that may help to control multidrug-resistant bacteria. In phage therapy, natural antagonists of bacteria, lytic phages, are harnessed to fight pathogens. In antimicrobial photodynamic therapy (aPDT), a photosensitizer, molecular oxygen, and light are used to produce reactive oxygen species (ROS) that inflict lethal damage on pathogens. Since aPDT destroys multiple essential components in targeted pathogens, aPDT resistance is unlikely. However, the challenge in aPDT is to maximize target specificity and minimize collateral oxidative damage to host cells. We now present an antimicrobial approach that combines the best features of both alternative therapies, namely, the high target specificity of phages and the efficacy of aPDT. This is achieved by conjugating the specific cell-binding domain from a phage protein to a near-infrared photosensitizer. aPDT with the resulting conjugate shows high target specificity toward MRSA with minimal side effects.